Pengembangan GURU CERDIG (Guru Cerdas Digital) dengan Bantuan AI untuk Perencanaan Pembelajaran Deep Learning di Sekolah Dasar Negeri Kabupaten Temanggung - Gati Destiyani; Bambang Ismanto; Stefanus Christian Relmasira (CV. Creative Tugu Pena, 2026)
The low level of students’ Higher-Order Thinking Skills (HOTS), as reflected in the 2022 Programme for International Student Assessment (PISA) results, together with the substantial administrative burden faced by teachers in developing high-quality deep learning lesson plans, remains a significant challenge in primary education. This study aimed to develop an AI-powered website-based platform called Guru Cerdig (Guru Cerdas Digital) to assist teachers in preparing instructional plans more efficiently and effectively. Product feasibility was evaluated using both qualitative and quantitative approaches, including validity and reliability testing, to ensure that the developed platform met acceptable standards of quality, consistency, and practical usability in educational settings. The study employed a Research and Development (R&D) methodology by integrating the ADDIE and Borg & Gall development models. Data were analyzed using a mixed-methods approach, utilizing MAXQDA for qualitative analysis and SPSS inferential statistical tests for quantitative analysis. The findings revealed that existing instructional planning practices remain largely dominated by conventional administrative procedures with limited pedagogical depth. The GURU CERDIG platform was rated as “Highly Feasible” by subject matter experts (93.83%) and IT/media experts (78.13%). From a practical perspective, the AI-powered features significantly reduced the time required to prepare instructional plans from several days to less than five minutes, with a user satisfaction rate of 48%. Furthermore, the Wilcoxon Signed-Rank Test produced a significance value of p < 0.001, indicating that the platform significantly improved the quality of instructional planning. The study concludes that GURU CERDIG represents a transformational digital ecosystem capable of enhancing teachers’ competence, efficiency, and confidence in implementing deep learning-oriented instructional practices.